2015
DOI: 10.1083/jcb.201412046
|View full text |Cite
|
Sign up to set email alerts
|

Axonal autophagosomes recruit dynein for retrograde transport through fusion with late endosomes

Abstract: Late endosome-loaded dynein–snapin complexes drive amphisome retrograde transport upon fusion of autophagosomes with late endosomes in distal axons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
235
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(263 citation statements)
references
References 38 publications
24
235
1
1
Order By: Relevance
“…From these experiments we concluded that BORC-dependent anterograde transport of lysosomes is important for mobilization and disposal of autophagosomes from the distal axon. This conclusion is consistent with the notion that fusion of lysosomes with autophagosomes contributes to the dynein-dependent retrograde transport of the resulting autolysosomes, in addition to the degradation of their contents (31,53).…”
Section: Reduced Growth Cone Dynamics and Aberrant Autophagosomes Insupporting
confidence: 80%
See 2 more Smart Citations
“…From these experiments we concluded that BORC-dependent anterograde transport of lysosomes is important for mobilization and disposal of autophagosomes from the distal axon. This conclusion is consistent with the notion that fusion of lysosomes with autophagosomes contributes to the dynein-dependent retrograde transport of the resulting autolysosomes, in addition to the degradation of their contents (31,53).…”
Section: Reduced Growth Cone Dynamics and Aberrant Autophagosomes Insupporting
confidence: 80%
“…The decreased size and dynamics of the growth cones in myrlysin-KD cells indicates a requirement of lysosomes for growth cone structure and function. We also observed that control neurons exhibited small vesicles labeled with the autophagy marker LC3, some that were stationary and others that moved mainly in the retrograde direction, as previously reported (30,31,52,53) (Fig. 7 E-H).…”
Section: Reduced Growth Cone Dynamics and Aberrant Autophagosomes Insupporting
confidence: 69%
See 1 more Smart Citation
“…9C). This model is supported by multiple studies that point to an active process of lysosome biogenesis within axons that begins with the merging of organelles derived from the endocytic and autophagic pathways followed by further maturation toward lysosomes that is coupled to their retrograde transport (44)(45)(46)(47)(48)(49). More specifically, there is a high level of constitutive autophagosome biogenesis that occurs within distal regions of axons (46,48,50,51).…”
Section: Discussionsupporting
confidence: 48%
“…More specifically, there is a high level of constitutive autophagosome biogenesis that occurs within distal regions of axons (46,48,50,51). These autophagosomes fuse with endosomes and acquire endocytic cargos and late endosome/lysosome marker proteins such as LAMP1 (46,48,49). These initial steps of convergence between the endocytic and autophagic pathways are accompanied by luminal acidification and coincide with a switch toward a predominantly dynein-driven transport in the retrograde direction (48,52).…”
Section: Discussionmentioning
confidence: 99%